Lanthanide bimetallic MOF-based fluorescent sensor for sensitive and visual detection of sulfamerazine and malachite. (1st June 2023) - Yue, Xiaoyue; Fu, Long; Li, Yan; Xu, Sheng; Lin, Xin; Bai, Yanhong
Graphical abstract: Highlights: Bimetallic Tb0.6 Eu0.4 -MOF was successfully synthesized by one-step solvothermal method at room temperature. Bimetallic Tb0.6 Eu0.4 -MOF could produce ratiometric fluorescence by itself. It was revealed that rapid detection of MG and SMZ could be achieved via IFE mechanism. A smartphone application was designed for assisting fluorescence sensor. Abstract: A lanthanide terbium/europium metal–organic framework (Tb0.6 Eu0.4 -MOF) was prepared by one-step solvothermal method at room temperature. A series of characterizations including scanning electron microscopy, powder X-ray diffraction spectra, Fourier transform infrared spectra and X-ray photoelectron spectroscopy were carried out to clarify the physical characteristics of the synthesized material. The data clarified that the prepared Tb0.6 Eu0.4 -MOF possessed rod-like morphology with a width of 1–2 μm, and had good crystal structure, good stability, response speed and excitation-independent emission feature. The bunchy Tb0.6 Eu0.4 -MOF was then used to construct fluorescent sensors for rapid identification of malachite green and sulfamerazine. It was revealed that the detection mechanism was inner filter effect. The effects of different parameters such as excitation wavelength and incubation times were investigated on the fluorescence analysis performance. The data clarified that the optimal excitation wavelength and incubation time was 240 nm and 3 min, respectively. The detection platform exhibited the high sensitivity and selectivity toward malachite green in the linear range of 2–180 μM and determined limit of detection was 1.12 μM. Besides, the proposed sensor allowed sensitive detection of sulfamerazine in the linear range of 2–140 μM with a low detection limit of 0.1 μM. Meaningfully, a smartphone application was designed to assist the proposed sensor to realize visual, intelligent and rapid detection of malachite green and sulfamerazine. Furthermore, the practical application of the proposed sensor has been also verified by high performance liquid chromatography, showing good accuracy, sensitivity and satisfactory recoveries. The results suggested that the Tb0.6 Eu0.4 -MOF-based ratiometric fluorescent sensor had the potential to become a promising technique for rapid detection of malachite green or sulfamerazine with smartphone application. Therefore, the prepared Tb0.6 Eu0.4 -MOF is one kind of efficient and cost-effective potential materials for developing fluorescent sensor for rapid, sensitive and selective detection of sulfamerazine and malachite.